PERAN BAWASLU PROVINSI RIAU DALAM MENUMBUHKAN PENGAWASAN PARTISIPATIF DI PROVINSI RIAU PADA PEMILU TAHUN 2024 - Devindra, M. Ilham D.; Nisaa, Fadhiilatun (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The implementation of participatory supervision plays a crucial role in maintaining the quality of democracy through active public involvement in the electoral process. In the context of the 2024 Election in Riau Province, the Election Supervisory Body (Bawaslu) of Riau Province holds a key role in optimizing participatory supervision through various designed programs. This research aims to describe how Bawaslu of Riau Province develops participatory supervision through the dimensions of governmental roles proposed by Ryaas Rasyid, as a regulator, facilitator, dynamizer, and catalyst. The study adopts a descriptive qualitative approach, with data collected through structured interviews, FGD, and documentation. The reaserch show that Bawaslu of Riau Province has implemented several participatory supervision programs, including the Participatory Supervision Education Program, Citizen Forums, Supervision Corners, Partnerships with Universities, Participatory Supervision Villages, and Digital Communities. Each program reflects the realization of Bawaslu’s role in developing participatory supervision during the 2024 Election. However, field implementation indicates that not all programs have been effectively carried out in accordance with Bawaslu’s roles as a regulator, facilitator, dynamizer, and catalyst. This research recommends expanding the reach and improving the quality of these programs, as well as enhancing citizens’ political literacy to strengthen participatory supervision and support a more transparent and inclusive electoral process. Keywords: Role, Bawaslu of Riau Province, Participatory Supervision, 2024 Election